Gadamer’s Hermeneutics And The Dynamics Of Islamic Democracy: A Study Of The Concept Of Al-Shūrā In Contemporary Contexts - Qustulani, Muhamad Qustulani; Murniasih,; Fahmi Irfani, (MIZAN: JOURNAL OF ISLAMIC LAW, 2025)
This study explores the application of Gadamer’s hermeneutic philosophy to the concept of Islamic democracy, emphasizing core principles such as al-shūrā (consultation), al-‘adālah (justice), al-musāwāh (equality), and al-ḥurriyyah (freedom) as dynamic and evolving meanings rather than fixed doctrines. Through the fusion of horizons, these values are continuously interpreted in dialogue with contemporary social realities, enabling pluralistic societies like Indonesia to foster tolerance, moderation, and inclusive participation. Central to this discourse is the concept of shūrā in the Qur’an, understood as consultation foundational to collective decision-making but not inherently identical to modern secular democracy. While critics reject equating shūrā with democracy due to conflicting views on sovereignty and law, proponents affirm its compatibility with democratic ideals grounded in Islamic values. Gadamer’s approach facilitates a contextual and moderate understanding of shūrā, positioning Islamic democracy as a living process of compassionate ijtihad that reconciles tradition and modernity, prioritizing pluralism and justice for peaceful coexistence.